Advances in pharmacotherapeutic management of common skin diseases in neonates and infants. (3rd May 2017) - Patrizi, Annalisa; Neri, Iria; Ricci, Giampaolo; Cipriani, Francesca; Ravaioli, Giulia Maria
ABSTRACT: Introduction : neonatal and infantile skin diseases are frequently encountered in the clinical practice and represent worldwide a socioeconomic issue. They encompass a wide range of acquired or congenital conditions, including infections, vascular lesions and inflammatory diseases and can present with different degrees of severity, leading in some cases to dramatic complications. Areas covered : In this paper we report the most recent evidences on the management of some common skin diseases in neonates and infants. Hemangiomas, viral, fungal and bacterial infections, omphalitis, atopic and seborrhoeic dermatitis, napkin disease will be treated and discussed. Expert opinion : The majority of the dermatologic alterations in neonates are physiological, transient and do not require any treatment, thus the parents can be reassured about the good prognosis. However, in some cases, serious conditions must be excluded. In particular neonatal and infantile infections should be promptly recognized and properly managed, to avoid severe complications. The therapeutic options include traditional and, although few, innovative medical treatments, which will be carefully taken into consideration by the expert Dermatologists and Paediatricians.